Approach and blokade of n. ischiadicus on the incisura ischiadica in Cattle (Bos taurus L.) - Mihelić, Damir; Bačić, Goran; Slavica, Alen Zobundžija, Mladen; Gjurčević-Kantura, Vesna Babić, Krešimir Brkić, Antun; Hincak, Zdravka (1995)
U radu je opisan pristup i blokada n. ischiadicus-a na incisuri ischiadici u goveda.
ENG